2018
DOI: 10.1186/s10020-018-0036-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the process of alternative RNA splicing results in soluble B and T lymphocyte attenuator with biological and clinical implications in critical illness

Abstract: BackgroundCritically ill patients with sepsis and acute respiratory distress syndrome have severely altered physiology and immune system modifications. RNA splicing is a basic molecular mechanism influenced by physiologic alterations. Immune checkpoint inhibitors, such as B and T Lymphocyte Attenuator (BTLA) have previously been shown to influence outcomes in critical illness. We hypothesize altered physiology in critical illness results in alternative RNA splicing of the immune checkpoint protein, BTLA, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…The soluble forms of CD27 can contribute to the activation of T cells and B cells 37,38 . In addition, previous studies have shown an increase in sBTLA levels in the blood of critically ill humans and mice 39 , and malignant melanoma cells express MHC-II, blinded sLAG-3 to up-regulate anti-apoptotic pathways 40 . Notably, at week 2 of sorafenib treatment, sCD27 levels were decreased from baseline ( Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The soluble forms of CD27 can contribute to the activation of T cells and B cells 37,38 . In addition, previous studies have shown an increase in sBTLA levels in the blood of critically ill humans and mice 39 , and malignant melanoma cells express MHC-II, blinded sLAG-3 to up-regulate anti-apoptotic pathways 40 . Notably, at week 2 of sorafenib treatment, sCD27 levels were decreased from baseline ( Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The splicing of BTLA-202 leads to loss of the transmembrane helix domain, resulting in a soluble BTLA product compared with the canonical isoform. This soluble isoform was confirmed and found to increase in the early stages of sepsis(51, 52) and was able to enhance antitumor activity in a melanoma pulmonary metastasis model in combination of HSP70 vaccine(53). Thus, the enrichment of T BTLA 202 cells in CD8+ exhausted T cells may suggest a new mechanism for the induction of immunosuppressive tumor microenvironment.…”
Section: Resultsmentioning
confidence: 83%
“…The BTLA gene structure is shown in Figure 4 . BTLA has three splicing variants: full length BTLA has five exons and possess a Ig-C like domain; the BTLA isoform with 70% extracellular domain missing due to a skipped exon 3 and soluble BTLA which lacks a fragment of exon 4 due to alternative 3’ splice site caused by a premature stop codon ( 209 ).…”
Section: B- and T-lymphocyte Attenuatormentioning
confidence: 99%